558 An Evaluation of Surgical Input and Management of Head Injury in a New Acute Hospital in South Wales: Does It Need to Be a Headache?. (19th August 2022) - Owen, A; David, E; Edwards, P
Abstract: Aim: The Grange University Hospital is a new major acute hospital in South Wales. Similarly, to other hospitals without neurosurgery, patients presenting to A&E with head injury (HI) that do not require transfer to a neurosurgery centre are admitted under general surgery. This audit aimed to: Quantify extent of surgical input in HI patients Evaluate the benefit of general surgical input in the management of HI Method: Patients admitted via A&E with the diagnosis code "Head Injury" (N=119) identified between November 28th-April 28 th, 2021 (6 months). Paediatric (Aged 0–18) patients (N=25) were excluded as identified admitting team as per protocol is paediatrics. Relevant data extracted using Clinical Workstation. Results: N =94 patients. Of these, 12 were discussed with neurosurgery and 1 patient transferred to a tertiary centre. 44% were referred to a surgical speciality other than general surgery for assessment. Despite this, of those 41, 61% (25) were admitted under general surgery (Average length of stay 2.5 days). Only 8 admitted patients necessitated plans beyond neuro observations. 28% of patients admitted under general surgery required medical assessment (4 falls assessments, 3 COTE referrals and subsequent takeovers). 0 patients had any general surgical pathology. Conclusions: Given low numbers of HI patients requiring neurosurgical opinion/ongoing surgical management there is no identified benefit to these patients being admitted under surgeons instead of medics. When a surgical pathology is identified, HI patients can be safely admitted under the speciality involved in their primary assessment and treatment, without general surgical input.